A EUROPEAN, MULTICENTRE, PHASE III, CLINICAL TRIAL OF HYPOTHERMIA FOR ACUTE ISCHAEMIC STROKE: EUROHYP-1 - Sprigg, N.; Smithson, J.; Bath, P.; Lees, K.; Macleod, M.; Van Der Worp, B.; Krieger, D.; Petersson, J.; Staykov, Dimitre; Schwab, Sibylle (2016)
EVALuna2:33132

Association of CamK2A genetic variants with transition time from occasional to regular heroin use in a sample of heroin-dependent individuals - Eirich, Antonia; Biermann, Teresa; Müller, Christian P.; Kornhuber, Johannes; Benyamin, Beben; Hulse, Gary K.; Wildenauer, Dieter B.; Schwab, Sibylle (Psychiatric Genetics, 2019)
Objectives Susceptibility to heroin dependence is strongly influenced by genetic factors with heritability estimates as high as 0.7. A number of genes, as well as environmental factors, are likely to contribute to its etiology. Not all individuals who have ever tried heroin at some stage during their lifetime become dependent on heroin. It has been suggested that genetic factors might be more important in the transition stage to heroin dependence rather than in environmental exposures and experimenting with heroin. As the features of substance dependence and memory formation have been found to be strikingly similar, we have focused on a key enzyme involved in long-term potentiation and synaptic plasticity, namely the calcium-dependent/calmodulin-dependent protein kinase IIa (CAMKIIa). We hypothesized, that CamK2A genetic variation may play a role in the transition from occasional to regular heroin use.
CRIS-Team WoS Importer:2019-02-27

Cerebrovascular complications of immunologically mediated heparin-induced thrombocytopenia - Macha, K.; Kloska, Stephan; Dörfler, Arnd; Raaz-Schrauder, D.; Schwab, Sibylle; Köhrmann, Martin; Seifert, Frank (Fortschritte der Neurologie - Psychiatrie, 2014)
Immunologically mediated heparin-induced thrombocytopenia (HIT) is a thrombotic disease caused by antibodies occurring after heparin exposure. Thrombocytopenia occurs within a few days after heparin exposure, about half of HIT-patients develop venous or arterial thrombotic complications. Neurological complications of HIT are mainly ischaemic stroke and sinus vein thrombosis. To ensure the primary clinical diagnosis functional and immunological assays for antibody detection are available. The probability for the occurrence of HIT depends on the nature of heparin employed (LMWH vs. UFH) and individual patient characteristics such as gender and primary disease (medical vs. surgical patients). In the case of suspected HIT heparin administration should be discontinued immediately and replaced by an alternative anticoagulation to prevent the expansion or development of further thrombotic complications. Herein we report a case of a patient suffering from HIT-associated embolic cerebral ischaemic stroke.
EVALuna2:22326

Dynamic Angiography and Perfusion Imaging Using Flat Detector CT in the Angiography Suite: A Pilot Study in Patients with Acute Middle Cerebral Artery Occlusions - Struffert, Tobias; Deuerling-Zheng, Y.; Kloska, Stephan; Engelhorn, Tobias; Lang, Sabine; Mennecke, Angelika; Manhart, M.; Strother, C. M.; Schwab, Sibylle; Dörfler, Arnd (American Journal of Neuroradiology, 2015)
Perfusion and angiographic imaging using intravenous contrast application to evaluate stroke patients is now technically feasible by flat detector CT performed by the angiographic system. The aim of this pilot study was to show the feasibility and qualitative comparability of a novel flat detector CT dynamic perfusion and angiographic imaging protocol in comparison with a multimodal stroke MR imaging protocol.In 12 patients with acute stroke, MR imaging and the novel flat detector CT protocol were performed before endovascular treatment. Perfusion parameter maps (MTT, TTP, CBV, CBF) and MIP/volume-rendering technique images obtained by using both modalities (MR imaging and flat detector CT) were compared.Comparison of MIP/volume-rendering technique images demonstrated equivalent visibility of the occlusion site. Qualitative comparison of perfusion parameter maps by using ASPECTS revealed high Pearson correlation coefficients for parameters CBF, MTT, and TTP (0.95-0.98), while for CBV, the coefficient was lower (0.49).We have shown the feasibility of a novel dynamic flat detector CT perfusion and angiographic protocol for the diagnosis and triage of patients with acute ischemic stroke. In a qualitative comparison, the parameter maps and MIP/volume-rendering technique images compared well with MR imaging. In our opinion, this flat detector CT application may substitute for multisection CT imaging in selected patients with acute stroke so that in the future, patients with acute stroke may be directly referred to the angiography suite, thereby avoiding transportation and saving time.
EVALuna2:22353

Early prediction of delayed cerebral ischemia in subarachnoid hemorrhage based on quantitative EEG: A prospective study in adults - Gollwitzer, S.; Groemer, Teja W.; Rampp, Stefan; Hagge, Mareike; Olmes, D.; Huttner, Hagen; Schwab, Sibylle; Madzar, D.; Hopfengaertner, R.; Hamer, Hajo (Clinical Neurophysiology, 2015)
Delayed cerebral infarction (DCI) has a significant impact on mortality and morbidity of patients with subarachnoid hemorrhage (SAH). The aim of this study was to define quantitative EEG (qEEG) parameters for the early and reliable prediction of DCI and compare the validity and time course of qEEG to standard procedures.12 consecutive unselected SAH patients (8 female, mean age 52 years, Hunt-and-Hess grade I-IV) were prospectively examined. Continuous six channel EEG monitoring was started within 48 h after admission (mean duration 5.2 days; range: 2-12 days). All raw and unselected EEG signal underwent automated artifact rejection, Short Time Fast Fourier Transformation and a detrending procedure in order to analyze regional spectral power changes in different frequency bands. According to clinical standards, transcranial Doppler sonography (TCD) was performed at least on alternate days and repeat cerebral computer tomography (CCT) as needed.6 patients (50%) developed vasospasm/DCI. Decrease of ?40% in power persisting over ?5h in the alpha band and ?6h in the theta band marked the optimal cut-off to detect DCI (sensitivity 89%, specificity 77% for alpha). EEG changes preceded detection of vasospasm/DCI in standard procedures by 2.3d ays. Changes in the beta and delta band as well as in the alpha/delta ratio demonstrated lower correlation with imminent DCI.Focal reduction in alpha power may represent a valid, observer independent, non-invasive and continuous marker for vasospasm/DCI in SAH patients.qEEG indicates imminent ischemia earlier than established diagnostic tools, such as TCD.
EVALuna2:22268

Gene expression imputation across multiple brain regions provides insights into schizophrenia risk - Huckins, Laura M.; Dobbyn, Amanda; Ruderfer, Douglas M.; Hoffman, Gabriel; Wang, Weiqing; Pardinas, Antonio F.; Rajagopal, Veera M.; Als, Thomas D.; Nguyen, Hoang T.; Girdhar, Kiran; Boocock, James; Roussos, Panos; et al. (Nature Genetics, 2019)
Transcriptomic imputation approaches combine eQTL reference panels with large-scale genotype data in order to test associations between disease and gene expression. These genic associations could elucidate signals in complex genome-wide association study (GWAS) loci and may disentangle the role of different tissues in disease development. We used the largest eQTL reference panel for the dorso-lateral prefrontal cortex (DLPFC) to create a set of gene expression predictors and demonstrate their utility. We applied DLPFC and 12 GTEx-brain predictors to 40,299 schizophrenia cases and 65,264 matched controls for a large transcriptomic imputation study of schizophrenia. We identified 413 genic associations across 13 brain regions. Stepwise conditioning identified 67 non-MHC genes, of which 14 did not fall within previous GWAS loci. We identified 36 significantly enriched pathways, including hexosaminidase-A deficiency, and multiple porphyric disorder pathways. We investigated developmental expression patterns among the 67 non-MHC genes and identified specific groups of pre- and postnatal expression.
CRIS-Team WoS Importer:2019-04-12

Impact of Perihemorrhagic Edema on Short-Term Outcome After Intracerebral Hemorrhage - Volbers, Bastian; Willfarth, Wolfgang; Schwab, Sibylle; Kuramatsu, J. B.; Huttner, Hagen; Struffert, Tobias; Dörfler, Arnd; Staykov, S. (Neurocritical Care, 2016)
Intracerebral hemorrhage (ICH) is a devastating disease with ICH volume being the main predictor of poor outcome. The prognostic role of perihemorrhagic edema (PHE) is still unclear; however, available data are mainly derived from analyses during the first days after symptom onset. As PHE growth may continue up to 14 days after ICH, we evaluated PHE over a longer period of time and investigated its impact on short-term clinical outcome.In this monocentric retrospective cohort study, patients with spontaneous supratentorial ICH were identified from our institutional data base. Different time points of CT scans were merged to time clusters for better comparison (day 1, 2-3, 4-6, 7-9, 10-12). Absolute volumes of ICH and PHE were obtained using a validated semiautomatic volumetric algorithm. Clinical outcome at discharge was assessed using the modified Rankin Scale (0-3 = favorable, 4-6 = poor).220 patients (83 with favorable, 137 with poor outcome) were included in the final analysis. Mean ICH volume on admission was 22.8 [standard deviation (SD) 24.6] cm(3). Mean absolute PHE volume on admission was 22.5 (SD 20.8) cm(3) and increased to a mean peak volume of 38.1 (SD 31.4) cm(3) during 6.7 (SD 4.1) days on average. Besides GCS on admission, functional status before ICH, peak hematoma volume, lobar localization and fever burden, and high peak PHE volume predicted poor outcome at discharge [OR 0.977 (95 % CI 0.957-0.998)] in the multivariable analysis.PHE may have a negative impact on short-term functional outcome after ICH and therefore represent a possible treatment target.
EVALuna2:22273

Intensive care therapy of space-occupying large hemispheric infarction. Summary of the NCS/DGNI guidelines - Boesell, J.; Schoenenberger, S.; Dohmen, C.; Juettler, E.; Staykov, D.; Zweckberger, K.; Hacke, W.; Schwab, Sibylle; Torbey, M. T.; Huttner, Hagen (Der Nervenarzt, 2015)
Large hemispheric infarction (LHI), synonymously called malignant middle cerebral artery (MCA) infarction, is a severe neurological disease with a high mortality and morbidity. Treating physicians as well as relatives are often faced with few and low quality data when attempting to apply optimal treatment to these patients and make decisions. While current stroke treatment guidelines focus on risk factors, prevention and acute management, they include only limited recommendations concerning intensive care management of LHI. The Neurocritical Care Society (NCS) and the German Society for Neurocritical and Emergency Medicine (DGNI) organized an interdisciplinary consensus conference on intensive care management of LHI to meet this demand. European and American experts in neurology, neurocritical care, neurosurgery, neuroradiology and neuroanesthesiology were selected based on their expertise and research focus. Subgroups for several main topics elaborated a number of central clinical questions concerning this topic and evaluated the quality of the currently available data according to the grading of recommendation assessment, development and evaluation (GRADE) guideline system. Subsequently, evidence-based recommendations were compiled after weighing the advantages against the disadvantages of certain management options. This is a commented abridged version of the results of the consensus conference.
EVALuna2:22396

Invasive neurology in focus - Schwab, Sibylle; Huttner, Hagen (Der Nervenarzt, 2016)
EVALuna2:22468

Invasive stroke treatment - Study results and clinical routine : Lost in translation? - Breuer, L.; Schwab, Sibylle; Köhrmann, Martin (Der Nervenarzt, 2016)
How can the overwhelmingly positive results of the five randomized thrombectomy trials published in 2015 be transferred to the clinical routine?Analysis of trial-specific characteristics with regard to implementation of mechanical thrombectomy into clinical routine.Stroke patients with symptomatic proximal artery occlusion are principally eligible for mechanical thrombectomy; however, the stroke patients included in the thrombectomy trials are not representative of all stroke patients. They were carefully selected according to clinical and imaging criteria as well as to the time window from symptom onset. Furthermore, they were treated in highly selected specialized stroke centers. Analysis of the five trials and the Catalan population-based SONIIA registry revealed that the observed number needed to treat (NNT) of 5 to reach a modified Rankin scale (mRS) score of 0-2 only applies to approximately 1 % of all stroke patients. The NNT for the remaining patients who are principally eligible for thrombectomy requires further study. Currently, centralization seems to be useful to facilitate mechanical thrombectomy in routine care leading to several problems that have to be dealt with in particular regions. Secondary transport to thrombectomy centers plays a major role in this context and has to be provided with highest priority.Only careful analysis of study results and the background circumstances will enable adequate organization and successful practical implementation of this highly effective therapy in the clinical routine. Regional conditions have to be considered and will be crucial in this context.
EVALuna2:22469

iPads in Breast Imaging - A Phantom Study - Hammon, Matthias; Schlechtweg, Philipp; Schulz-Wendtland, Rüdiger; Uder, Michael; Schwab, Sibylle (Geburtshilfe und Frauenheilkunde, 2014)
Introduction: Modern tablet PCs as the iPad are becoming more and more integrated into medicine. The aim of this study was to evaluate the display quality of iPads regarding digital mammography. Materials and Methods: Three experienced readers compared the display quality of the iPad 2 and 3 with a dedicated 10 megapixel (MP) mammography liquid crystal display (LCD) screen in consensus using the standardized Contrast Detail Mammography (CDMAM) phantom. Phantom fields without agreement between the readers were classified as "uncertain", correct 2 : 1 decisions were classified as "uncertain/readable". In a second step display quality of the three reading devices was judged subjectively in a side by side comparison. Results: The 10 MP screen was superior to both iPads in 4 (phantom-)fields and inferior in 2 fields. Comparing the iPads, version 3 was superior in 4 fields and version 2 was superior in 1 field. However these differences were not significant. Total number of "uncertain" fields did not show significant differences. The number of "uncertain" fields was 15 with the 10 MP screen, 16 with the iPad 2 and 17 with the iPad 3 (p > 0.05), the number of "uncertain/readable" fields was 4, 7 and 8, respectively. Subjective image quality of the iPad 3 and the 10 MP screen was rated superior to the iPad 2. Conclusion: The evaluated iPads, especially in version 3, seem to be adequate to display mammograms in a diagnostic quality and thus could be useful e.g. for patient consultation, clinical demonstration or educational and teaching purposes. However primary mammogram reading should still be performed on dedicated large sized reading screens.
EVALuna2:14368

Parenchymatous hemorrhage is associated with unfavorable longterm outcome in patients with atraumatic subarachnoid hemorrhage - Gerner, Stefan; Kuramatsu, J.; Reichl, J.; Eyüpoglu, Ilker Yasin; Buchfelder, Michael; Dörfler, Arnd; Struffert, Tobias; Schwab, Sibylle; Huttner, Hagen (2017)
EVALuna2:34024

Possible second motor neuron damage in neuromyelitis optica - Laemmer, A. B.; Maihöfner, Christian; Gölitz, Philipp; Schwab, Sibylle; Lee, D. H.; Linker, R. A.; Schramm, Axel (Clinical Neurophysiology, 2014)
EVALuna2:22245

Publisher Correction: Gene expression imputation across multiple brain regions provides insights into schizophrenia risk (Nature Genetics, (2019), 51, 4, (659-674), 10.1038/s41588-019-0364-4) - Huckins, Laura M.; Dobbyn, Amanda; Hoffman, Gabriel; Wang, Weiqing; Pardiñas, Antonio F.; T. Nguyen, Hoang; Girdhar, Kiran; Boocock, James; Roussos, Panos; Fromer, Menachem; Kramer, Robin; Domenici, Enrico; et al. (Nature Genetics, 2019)
In the HTML version of the article originally published, the author group ‘The Schizophrenia Working Group of the Psychiatric Genomics Consortium’ was displayed incorrectly. The error has been corrected in the HTML version of the article.
CRIS-Team Scopus Importer:2019-05-28

Rheumatoid vasculitis of the central nervous system - Lee, D. H.; Blinzler, C.; Stöckl, Thomas; Engelhorn, Tobias; Buslei, R.; Schwab, Sibylle; Linker, Ralf (Der Nervenarzt, 2015)
EVALuna2:7259

Secretion of acid Sphingomyelinase is affected by its polymorphic signal peptide - Rhein, Cosima; Reichel, Martin; Mühle, Christiane; Rotter, Andrea; Schwab, Sibylle; Kornhuber, Johannes (Cellular Physiology and Biochemistry, 2014)
Acid sphingomyelinase (ASM) catalyses the hydrolysis of sphingomyelin into ceramide, which acts as a lipid messenger that regulates important cellular functions. Deregulated ASM activity has been reported for different common diseases, but the mechanisms regulating ASM activity are still debated. ASM contains an exceptional signal peptide which is polymorphic due to a variable number of a hexanucleotide sequence that determines the length of the hydrophobic core. We investigated the impact of the signal peptide polymorphism on the regulation of ASM activity and secretion in vivo and in vitro.Subjects homozygous for the rare 4-repeat allele displayed significantly lower secreted ASM activity than subjects homozygous for the common 6-repeat allele. In vitro, overexpression of ASM variants encoded by 2, 8 or 9 repeats resulted in a significantly lowered ASM secretion rate. Treatment of ASM-overexpressing cells with tumour necrosis factor ? induced secretion of ASM, and the secretion rate was highest for the most common ASM variant encoding 6 repeats compared to other naturally occurring variants.We provide evidence that the polymorphic ASM signal peptide regulates ASM secretion. It might be an evolutionary mechanism to increase ASM secretion potential, whereas an increase in lysosomal ASM activity is limited due to deleterious cellular effects.
EVALuna2:23668

Specialized neurological neurosurgical intensive care medicine - Kuramatsu, J. B.; Huttner, Hagen; Schwab, Sibylle (Der Nervenarzt, 2016)
In Germany dedicated neurological-neurosurgical critical care (NCC) is the fastest growing specialty and one of the five big disciplines integrated within the German critical care society (Deutsche Interdisziplinäre Vereinigung für Intensiv- und Notfallmedizin; DIVI). High-quality investigations based on resilient evidence have underlined the need for technical advances, timely optimization of therapeutic procedures, and multidisciplinary team-work to treat those critically ill patients. This evolution has repeatedly raised questions, whether NCC-units should be run independently or better be incorporated within multidisciplinary critical care units, whether treatment variations exist that impact clinical outcome, and whether nowadays NCC-units can operate cost-efficiently? Stroke is the most frequent disease entity treated on NCC-units, one of the most common causes of death in Germany leading to a great socio-economic burden due to long-term disabled patients. The main aim of NCC employs surveillance of structural and functional integrity of the central nervous system as well as the avoidance of secondary brain damage. However, clinical evaluation of these severely injured commonly sedated and mechanically ventilated patients is challenging and highlights the importance of neuromonitoring to detect secondary damaging mechanisms. This multimodal strategy not only requires medical expertise but also enforces the need for specialized teams consisting of qualified nurses, technical assistants and medical therapists. The present article reviews most recent data and tries to answer the aforementioned questions.
EVALuna2:22466

Teaching NeuroImages: Stroke and bilateral visual loss in a young adult: More than coincidence - Volbers, Bastian; Kaldefoss, K.; Bergua, A.; Kloska, Stephan; Schwab, Sibylle; Köhrmann, Martin (Neurology, 2012)
EVALuna2:21072

Telemedicine: Comprehensive coverage and quality - Not a contradiction : Practical experience from the stroke network with telemedicine in northern Bavaria (STENO) - Breuer, Lorenz; Erbguth, F.; Oschmann, P.; Schwab, Sibylle (Der Nervenarzt, 2017)
Telemedicine is widely used in the field of stroke treatment. Following the pioneering and implementation phase, the quality of the whole stroke treatment process needs to be ensured in telemedically connected hospitals. This is particular important for telestroke hospitals without neurological expertise and can be achieved by integrating telemedicine into the stroke unit concept and stroke networks. The Stroke Network with Telemedicine in Northern Bavaria (STENO) provides an example of how quality management can be practically implemented. The implementation of STENO has established a network-wide quality management system which has been certified according to DIN EN ISO 9001:2008 since 2011.
EVALuna2:22530

Telemedicine in stroke care - Breuer, Lorenz; Schwab, Sibylle (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2017)
Telemedicine is already widely used in many telestroke networks and ensures stroke treatment close to the patient's home in rural and medically underserved areas. This is particularly effective when telemedicine is integrated into a stroke unit concept. While telemedically based thrombolysis therapy has become routine practice for many years, practical implementation of comprehensive mechanical thrombectomy and the related processes remains challenging. The main tasks for the future further include development of a structured stroke aftercare system in neurologically underserved areas and permanent assurance of high-quality stroke care in telemedically connected sites.
EVALuna2:22560

The common acid sphingomyelinase polymorphism p.G508R is associated with self-reported allergy - Reichel, Martin; Richter-Schmidinger, Tanja; Mühle, Christiane; Rhein, Cosima; Alexopoulos, Panagiotis; Schwab, Sibylle; Gulbins, Erich; Kornhuber, Johannes (Cellular Physiology and Biochemistry, 2014)
Acid sphingomyelinase (ASM) is a key regulator of ceramide-dependent signalling pathways. Among others, activation of ASM can be induced by CD95 or cytokine signalling and by cellular stress resulting from inflammation or infection. Increased ASM activity was observed in a variety of human diseases including inflammatory and neuropsychiatric disorders. We hypothesized that basal ASM activity might influence the susceptibility for common human diseases.The general health condition of 100 young people was assessed using a questionnaire. The ASM polymorphism rs1050239 (c.1522G>A; encoding p.G508R) was determined from genomic DNA. Activities of secretory (S-) and lysosomal (L-) ASM were measured in blood plasma and peripheral blood cells respectively.The polymorphism rs1050239 was significantly associated with self-reported allergy (p=4.68×10(-4); adjusted p-value for multiple testing 0.007). Allergy was more prevalent in carriers of the minor A allele compared to non-carriers (p=0.00015; odds ratio=6.5, 95% CI 2.15-21.7). S-ASM activity was significantly associated with rs1050239 (p=5.3×10(-7)) and decreased with the number of A alleles in a gene-dosage dependent manner. In allergic patients, S-ASM activity was moderately decreased (p=0.034). L-ASM activity was significantly lower in subjects homozygous for the minor A allele (p=0.025) but not different between allergic and non-allergic subjects (p=0.318).Our analysis provides evidence for an involvement of ASM in the pathophysiology of allergy, which is in line with previous reports addressing the role of sphingolipids in this disorder. Further studies should clarify the mechanism linking rs1050239 to allergy. The ASM pathway might be useful for predicting allergic disposition and disease course and as a therapeutic target.
EVALuna2:23677

The priority aim is to survive the intensive care unit but that alone is not sufficient: The neurological and mental sequelae of intensive medical care treatment - Kapfhammer, H. -P.; Schwab, Sibylle (Der Nervenarzt, 2016)
EVALuna2:22463

"Time is brain" in relapsing remitting multiple sclerosis : Current treatment concepts in immunotherapy - Linker, Ralf; Kallmann, B. -A.; Kleinschnitz, C.; Rieckmann, P.; Maeurer, M.; Schwab, Sibylle (Der Nervenarzt, 2015)
Despite highly divergent time scales of disease evolution in multiple sclerosis (MS) and ischemic stroke, clear analogies are apparent that may point the way to optimization of MS treatment. Inflammatory disease activity and neurodegeneration may induce potentially irreversible damage to central nervous system structures and thus lead to permanent disability. For the treatment of MS early detection of disease activity and early immunotherapy or treatment optimization are pivotal determinants of long-term outcomes. Such therapeutic concepts may be described with the catchy phrase "time is brain" as coined for the acute thrombolytic treatment of ischemic stroke.For MS a "time is brain" concept would comprise an early initiation of first line therapy as well as sensitive and structured monitoring of disease activity under therapy in conjunction with a low threshold for timely treatment optimization to achieve sustained freedom from measurable disease activity. This approach may substantially improve the long-term outcome in patients who show insufficient response to platform therapies. The intersectorial collaboration in regional MS care networks involving office-based neurologists and specialized MS centers may facilitate the timely use of highly active therapies with their specific benefit-risk profiles thus supporting sustained stabilization of patient quality of life.
EVALuna2:22369

Treatment of stroke - Koehrmann, M.; Schwab, Sibylle (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2017)
EVALuna2:33130